Sodium-ion battery positive electrode material precursor, preparation method thereof and positive electrode material

By using Ce-doped BaMnO3 or its composite ZnO as a cladding layer, combined with a layered hydroxide precursor, the problem of insufficient conductivity and thermal stability of BaMnO3 in sodium ion batteries is solved, and the electricity of sodium ion batteries is significantly improved. Chemical properties and cyclic stability.

CN119191388AActive Publication Date: 2024-12-27PAWA (ZHUJI) NEW ENERGY TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411678852.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-27
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

As the precursor of the positive electrode material of sodium ion battery, BaMnO3 has problems such as insufficient conductivity, poor thermal stability and poor circulation performance, which limits the performance improvement of sodium ion battery.

Method used

Ce-doped BaMnO3 or Ce-doped BaMnO3 composite ZnO is used as the cladding layer, and combined with a layered hydroxide precursor, it is used as the precursor of the positive electrode material of sodium ion battery through the preparation method to improve conductivity and thermal stability.

Benefits of technology

The electrochemical performance and cycle stability of sodium ion batteries have been significantly improved, and the problem of insufficient electrochemical performance may exist in single Ce doped BaMnO3 or ZnO doped.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191388A_ABST
    Figure CN119191388A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode material precursor, a preparation method thereof and a positive electrode material. The sodium ion battery positive electrode material precursor comprises a layered hydroxide precursor and a coating layer coating at least part of the surface of the layered hydroxide precursor; wherein the coating layer is made of a Ce (cerium) doped BaMnO3 material or a Ce doped BaMnO3 composite ZnO material. According to the invention, Ce is used for doping BaMnO3, so that the electrical conductivity and thermal stability of BaMnO3 are improved under the condition that the structural stability of BaMnO3 is ensured, and therefore, when Ce-doped BaMnO3 is used as a coating material of a precursor of a sodium-ion battery positive electrode material, the performance of a sodium-ion battery can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material precursor and a preparation method thereof, and a positive electrode material. Background Art

[0002] As the demand for renewable energy continues to grow, sodium-ion batteries have gradually attracted widespread attention as a cost-effective and resource-rich energy storage solution. At present, the cathode materials of sodium-ion batteries are mainly layered oxides, such as sodium nickel iron manganese oxide (NFM), sodium manganese oxide (NMO), etc. The choice of cathode materials directly determines the battery performance and application prospects. However, layered oxides have problems such as structural instability and short cycle life. Therefore, researchers often improve material performance by coating and modifying the cathode materials or their precursors.

[0003] BaMnO3 has a perovskite structure that can provide better intercalation ability for sodium ions, and it has excellent electrochemical properties and relatively low cost, so it has attracted much attention in the battery field. However, BaMnO3 has problems such as insufficient conductivity, poor thermal stability and poor cycle performance in practical applications. When it is used as a coating material for the positive electrode material precursor, the improvement of the performance of the positive electrode material of the sodium ion battery is very limited. Therefore, how to improve the defects of the BaMnO3 coating material is very critical to further improve the performance of the sodium ion battery. Summary of the invention

[0004] The purpose of the present invention is to provide a sodium ion battery positive electrode material precursor and a preparation method thereof and a positive electrode material, so as to further improve the electrochemical performance of the sodium ion battery positive electrode.

[0005] In the first aspect, the present invention provides a sodium ion battery positive electrode material precursor, which adopts the following technical solution: A sodium ion battery positive electrode material precursor comprises a layered hydroxide precursor and a coating layer coated on at least a portion of the surface of the layered hydroxide precursor; wherein the coating layer is a Ce-doped BaMnO3 material or a Ce-doped BaMnO3 composite ZnO material.

[0006] Preferably, the molar ratio of Ba, Mn and Ce elements in the Ce-doped BaMnO3 is 1:1-x:x, 0.01≤x≤0.1.

[0007] Preferably, in the Ce-doped BaMnO3 composite ZnO material, the mass ratio of Ce-doped BaMnO3 to ZnO is (1-3):(1-3).

[0008] Preferably, the mass of the coating layer is 1-20% of the mass of the layered hydroxide precursor.

[0009] Preferably, the layered hydroxide precursor is one of nickel-iron-manganese hydroxide, nickel-iron-copper-manganese hydroxide, copper-iron-manganese hydroxide, nickel-manganese-copper hydroxide, and nickel-zinc-iron-manganese hydroxide; More preferably, the layered hydroxide precursor is: Ni x Fe y Mn z (OH)2, 0.3≤x≤0.8, 0<y≤0.4, 0<z≤0.4, x+y+z=1; or Ni a Cu b Fe c Mn d (OH)2, 0.2≤a≤0.5, 0.05<b≤0.3, 0.2≤c≤0.4, 0.1≤d≤0.5, a+b+c+d=1.

[0010] In a second aspect, the present invention provides a method for preparing a precursor of a positive electrode material for a sodium ion battery, comprising the following steps: S1: Mix and dissolve a barium source, a manganese source, a cerium source, and a complexing agent in water, stir and mix evenly, heat and evaporate to dryness, and then further dry and calcine to obtain Ce-doped BaMnO3 powder; S2: dispersing Ce-doped BaMnO3 powder or a mixed powder consisting of Ce-doped BaMnO3 powder and ZnO powder in an alcohol solvent to obtain a dispersion; dispersing a layered hydroxide precursor in the dispersion, stirring and evaporating to obtain a solid; after the solid is dried, heating and then keeping warm under a protective atmosphere to obtain a precursor of a positive electrode material for a sodium ion battery.

[0011] Preferably, in step S1, the barium source, manganese source and cerium source are water-soluble salts of barium, manganese and cerium respectively, and more preferably barium nitrate, manganese nitrate and cerium nitrate; the barium source, manganese source and cerium source are added according to the molar ratio of Ba, Mn and Ce of 1:1-x:x, 0.01≤x≤0.1.

[0012] Preferably, in step S1, the complexing agent is one or more of citric acid, urea, and polyethylene glycol, and the ratio of the molar number of the complexing agent to the total molar number of Ba, Mn, and Ce ions in the barium source, manganese source, and cerium source is 1-2:1.

[0013] Preferably, in step S1, the heating evaporation temperature is 80-100°C; the drying temperature is 80-150°C, and the drying time is 8-12 hours; the calcination temperature is 700-1000°C, and the calcination time is 10-24 hours.

[0014] Preferably, in step S2, the amount of Ce-doped BaMnO3 powder added is 1-10wt% of the amount of layered hydroxide precursor added; the amount of ZnO powder added is 1-10wt% of the amount of layered hydroxide precursor added; and the alcohol solvent is anhydrous ethanol.

[0015] Preferably, in step S2, the stirring evaporation temperature is 80-150° C.; the drying temperature is 100-120° C., and the drying time is 8-12 h; the insulation temperature is 200-400° C., and the insulation time is 0.5-5 h.

[0016] In a third aspect, the present invention provides a sodium ion battery positive electrode material, which is obtained by mixing the aforementioned sodium ion battery positive electrode material precursor with a sodium source and sintering; Preferably, the sodium source is one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium acetate, and sodium oxalate, more preferably sodium carbonate.

[0017] Preferably, the mixing ratio of the sodium ion battery positive electrode material precursor and the sodium source is 1 to 1.1.

[0018] The sodium mixing ratio is the ratio of the molar number of Na to the total molar number of metal elements in the precursor of the positive electrode material of the sodium ion battery; that is, if the precursor of the positive electrode material of the sodium ion battery is Ni x Fe y Mn z (OH)2, the sodium mixing ratio is the ratio of the molar number of Na to the total molar number of Ni, Fe and Mn.

[0019] Preferably, the sintering temperature is 700-950°C.

[0020] In a fourth aspect, the present invention provides a sodium ion battery comprising the aforementioned sodium ion battery positive electrode material.

[0021] Beneficial effects of the present invention: 1) After the present invention dopes BaMnO3 with Ce, the electrical conductivity and thermal stability of BaMnO3 are improved while ensuring the structural stability of BaMnO3. Therefore, when Ce-doped BaMnO3 is used as a coating material for a precursor of a positive electrode material for a sodium ion battery, the performance of the sodium ion battery can be significantly improved.

[0022] 2) In the present invention, Ce-doped BaMnO3 composite ZnO material is used as the coating layer of the precursor of the positive electrode material of the sodium ion battery, mainly because ZnO has good stability and can play a good protective role on the positive electrode material, while Ce-doped BaMnO3 has structural advantages and good conductivity, can provide better intercalation ability for sodium ions, and can form a good conductive network on the surface of the positive electrode material. Therefore, the composite of the two materials can further improve the electronic conductivity and cycle stability of the positive electrode material, and overcome the problem of insufficient electrochemical performance that may exist in single Ce-doped BaMnO3 or ZnO doping. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1 of the present invention.

[0024] Figure 2 This is a SEM image of the positive electrode material prepared in Example 2 of the present invention.

[0025] Figure 3 Electrochemical performance diagram of batteries assembled with the positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3.

[0026] Figure 4 Electrochemical performance diagram of batteries assembled with positive electrode materials prepared in Examples 5 to 7 and Comparative Example 4.

[0027] Figure 5 Electrochemical performance diagram of batteries assembled with the positive electrode materials prepared in Examples 8 and 9. DETAILED DESCRIPTION

[0028] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0029] Preparation Example 1 Preparation of Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 Add pure water to the reactor to 1 / 2 of the volume, then introduce 6.5g / L ammonia water as a complexing agent and 4.5mol / L sodium hydroxide as a precipitant to form a bottom liquid with a pH of 12, and then introduce nitrogen to keep the oxygen concentration in the reactor below 0.5%. Nickel sulfate hexahydrate, ferrous sulfate heptahydrate, and manganese sulfate tetrahydrate are weighed and dissolved in water according to a Ni:Fe:Mn molar ratio of 1:1:1. The total metal ion concentration is 3.6mol / L to obtain a metal salt solution. The metal salt solution, 4.5mol / L sodium hydroxide, and 6.5g / L ammonia water are passed into the reactor for co-precipitation reaction. The reaction is stopped when the synthetic particle size is 5μm; the temperature of the entire reaction process is controlled at 60°C, the pH is 11-12, and the stirring rate is 500rpm. The precursor slurry after the reaction is filtered, washed, and dried at 130°C for 10h to obtain Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2.

[0030] Preparation Example 2 Preparation of Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2 Add pure water to the reactor to 1 / 2 of the volume, then introduce 6.5g / L ammonia water as a complexing agent and 4.5mol / L sodium hydroxide as a precipitant to form a bottom liquid with a pH of 11.5, and then introduce nitrogen to keep the oxygen concentration in the reactor below 0.5%. Weigh nickel sulfate hexahydrate, copper sulfate pentahydrate, ferrous sulfate heptahydrate, and manganese sulfate tetrahydrate and dissolve them in water according to the molar ratio of Ni:Cu:Fe:Mn of 2:1:3:3, and the total metal ion concentration is 3.0mol / L to obtain a metal salt solution. The metal salt solution, 4.5mol / L sodium hydroxide, and 6.5g / L ammonia water are passed into the reactor for co-precipitation reaction. The reaction is stopped when the synthetic particle size is 5μm; the temperature of the entire reaction process is controlled at 60°C, the pH is 11-12, and the stirring rate is 350rpm. The precursor slurry after the reaction is filtered, washed, and dried at 130°C for 12h to obtain Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2.

[0031] Example 1 In this embodiment, the layered hydroxide precursor in the sodium ion battery positive electrode material precursor is Ni prepared in Preparation Example 1. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2; the coating layer is Ce-doped BaMnO3 composite ZnO material.

[0032] The method for preparing a precursor of a positive electrode material for a sodium ion battery in this embodiment comprises the following steps: (1) Weigh barium nitrate, manganese nitrate, cerium nitrate and citric acid, stir and dissolve them in water to obtain a mixed solution, wherein: barium nitrate, manganese nitrate and cerium nitrate are added according to the molar ratio of Ba, Mn and Ce of 1:0.95:0.05, and the ratio of the molar number of citric acid to the total molar number of Ba, Mn and Ce ions in barium nitrate, manganese nitrate and cerium nitrate is 1.2:1; the mixed solution is stirred and evaporated to dryness at 90°C, and dried at 120°C for 10 hours to obtain a powder; then the powder is placed in a muffle furnace at 800°C and calcined for 15 hours to obtain Ce-doped BaMnO3 powder.

[0033] (2) Take the Ce-doped BaMnO3 powder and ZnO powder in step (1) in anhydrous ethanol, stir and ultrasonicate for 2 hours to obtain a dispersion; add the Ni prepared in Preparation Example 1 to the dispersion. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, continue stirring and ultrasonic for 3h, evaporate to dryness with stirring at 90℃, dry in an oven at 120℃ for 10h, and then keep warm at 300℃ for 3h under protective atmosphere to obtain Ce-doped BaMnO3 composite ZnO-coated sodium ion battery positive electrode material precursor. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 added at 5wt%.

[0034] Preparation of positive electrode materials for sodium ion batteries: The prepared Ce-doped BaMnO3 composite ZnO-coated sodium ion battery positive electrode material precursor was mixed evenly with anhydrous sodium carbonate at a mixing ratio of 1.05, and then sintered in a muffle furnace at 850°C for 20h to obtain the positive electrode material Ce-doped BaMnO3 composite ZnO-coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0035] The SEM image of the positive electrode material prepared in Example 1 of the present invention is as follows: Figure 1 As shown, it can be seen that the primary particles of the prepared positive electrode material are flaky and spherical as a whole, and the coating layer is tightly coated on the surface of the material without agglomeration.

[0036] Example 2 The method is basically the same as Example 1, except that the coating layer is Ce-doped BaMnO3 and does not contain ZnO; that is, ZnO powder is not added in step (2), and the amount of Ce-doped BaMnO3 powder added is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3The amount of (OH)2 added was 10wt%; the prepared precursor was: Ce-doped BaMnO3-coated Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, the positive electrode material is Ce-doped BaMnO3 coated NaNi 1 / 3Fe 1 / 3 Mn 1 / 3 O2.

[0037] The SEM image of the positive electrode material prepared in Example 2 of the present invention is as follows: Figure 2 As shown, it can be seen that the primary particles of the prepared positive electrode material are flaky and spherical as a whole, and the coating layer is tightly coated on the surface of the material without agglomeration.

[0038] Comparative Example 1 Directly use the Ni prepared in Preparation Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 was used as a precursor without coating; according to the preparation method of the positive electrode material for sodium ion battery in Example 1, the precursor was mixed with sodium carbonate and sintered to prepare the positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0039] Comparative Example 2 The difference from Example 2 is that the coating layer is BaMnO3; the preparation method of the corresponding BaMnO3 is as follows: Preparation of BaMnO3: Weigh barium nitrate, manganese nitrate and citric acid, stir and dissolve them in water to obtain a mixed solution, wherein: barium nitrate and manganese nitrate are added in a molar ratio of Ba to Mn of 1:1, and the ratio of the molar number of citric acid to the total molar number of Ba and Mn ions in barium nitrate and manganese nitrate is 1.2:1; the mixed solution is stirred and evaporated to dryness at 90°C, and dried at 120°C for 10 hours, and then the dried powder is placed in a muffle furnace at 800°C and calcined for 15 hours to obtain BaMnO3 powder.

[0040] The rest of the preparation method is the same as in Example 2, and the corresponding precursor prepared is BaMnO3-coated Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, the positive electrode material is BaMnO3 coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0041] Comparative Example 3 The method is basically the same as Example 1, except that ZnO is directly used as the coating layer; that is, Ce-doped BaMnO3 powder is not added in step (2), and the amount of ZnO powder added is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The amount of (OH)2 added was 10wt%; the corresponding precursor was ZnO-coated Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, the positive electrode material is ZnO-coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0042] Example 3 It is basically the same as Example 1, except that, during the preparation of Ce-doped BaMnO3, barium nitrate, manganese nitrate and cerium nitrate are added according to the molar ratio of Ba, Mn and Ce of 1:0.99:0.01.

[0043] Example 4 It is basically the same as Example 1, except that, during the preparation of Ce-doped BaMnO3, barium nitrate, manganese nitrate and cerium nitrate are added according to the molar ratio of Ba, Mn and Ce of 1:0.9:0.1.

[0044] Example 5 The same as Example 1, except that the layered hydroxide precursor is Ni prepared in Preparation Example 2. 2 / 9Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2, the prepared precursor is: Ce-doped BaMnO3 composite ZnO-coated Ni 2 / 9 Cu 1 / 9 Fe 1 / 3Mn 1 / 3 (OH)2, the positive electrode material is Ce-doped BaMnO3 composite ZnO-coated NaNi 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 O2.

[0045] Comparative Example 4 Directly use the Ni prepared in Preparation Example 2 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2 was used as a precursor without coating. According to the preparation method of the positive electrode material for sodium ion battery in Example 5, the precursor was mixed with sodium carbonate and sintered to prepare the positive electrode material NaNi2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 O2.

[0046] Example 6 The same as Example 5, except that the addition amount of Ce-doped BaMnO3 powder is Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The amount of (OH)2 added was 7.5wt%, and the amount of ZnO powder added was Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2 added amount is 2.5wt%.

[0047] Example 7 The same as Example 5, except that the addition amount of Ce-doped BaMnO3 powder is Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 The amount of (OH)2 added was 2.5wt%, and the amount of ZnO powder added was Ni 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 (OH)2 added amount is 7.5wt%.

[0048] Example 8 In this embodiment, the layered hydroxide precursor in the sodium ion battery positive electrode material precursor is Ni prepared in Preparation Example 1. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2; the coating layer is Ce-doped BaMnO3 composite ZnO material.

[0049] The method for preparing a precursor of a positive electrode material for a sodium ion battery in this embodiment comprises the following steps: (1) Weigh barium nitrate, manganese nitrate, cerium nitrate and citric acid, stir and dissolve them in water to obtain a mixed solution, wherein barium nitrate, manganese nitrate and cerium nitrate are added according to the molar ratio of Ba, Mn and Ce of 1:0.97:0.03, and the ratio of the molar number of citric acid to the total molar number of Ba, Mn and Ce ions in barium nitrate, manganese nitrate and cerium nitrate is 1.7:1; the mixed solution is stirred and evaporated to dryness at 100°C, and dried at 150°C for 8h, and then the dried powder is placed in a muffle furnace at 700°C and calcined for 22h to obtain Ce-doped BaMnO3 powder.

[0050] (2) Take the Ce-doped BaMnO3 powder and ZnO powder in step (1) in anhydrous ethanol, stir and ultrasonicate for 2 hours to obtain a dispersion; add the Ni prepared in Preparation Example 1 to the dispersion. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, continue stirring and ultrasonic treatment for 2h, evaporate to dryness with stirring at 80℃, dry in an oven at 100℃ for 12h, and then keep warm at 200℃ for 5h under protective atmosphere to obtain Ce-doped BaMnO3 composite ZnO-coated sodium ion battery positive electrode material precursor. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 added amount is 2wt%.

[0051] Preparation of positive electrode materials for sodium ion batteries: The prepared Ce-doped BaMnO3 composite ZnO-coated sodium ion battery positive electrode material precursor was mixed evenly with anhydrous sodium carbonate at a mixing ratio of 1.1, and then sintered in a muffle furnace at 700°C for 30h to obtain the positive electrode material Ce-doped BaMnO3 composite ZnO-coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0052] Example 9 In this embodiment, the layered hydroxide precursor in the sodium ion battery positive electrode material precursor is Ni prepared in Preparation Example 1. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2; the coating layer is Ce-doped BaMnO3 composite ZnO material.

[0053] The method for preparing a precursor of a positive electrode material for a sodium ion battery in this embodiment comprises the following steps: (1) Weigh barium nitrate, manganese nitrate, cerium nitrate and urea, stir and dissolve them in water to obtain a mixed solution, wherein barium nitrate, manganese nitrate and cerium nitrate are added according to the molar ratio of Ba, Mn and Ce of 1:0.93:0.07, and the ratio of the molar number of urea to the total molar number of Ba, Mn and Ce ions in barium nitrate, manganese nitrate and cerium nitrate is 1:1; the mixed solution is stirred and evaporated to dryness at 80°C, and dried at 100°C for 12 hours to obtain a powder; then the powder is calcined in a muffle furnace at 950°C for 10 hours to obtain Ce-doped BaMnO3 powder.

[0054] (2) Take the Ce-doped BaMnO3 powder and ZnO powder in step (1) in anhydrous ethanol, stir and ultrasonicate for 2 hours to obtain a dispersion; add the Ni prepared in Preparation Example 1 to the dispersion. 1 / 3 Fe 1 / 3 Mn1 / 3 (OH)2, continue stirring and ultrasonic for 4h, evaporate to dryness at 150℃, dry in an oven at 120℃ for 8h, and then keep warm at 400℃ for 1h under protective atmosphere to obtain Ce-doped BaMnO3 composite ZnO-coated sodium ion battery positive electrode material precursor. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 added amount 10wt%.

[0055] Preparation of positive electrode materials for sodium ion batteries: The prepared Ce-doped BaMnO3 composite ZnO-coated sodium ion battery positive electrode material precursor was mixed evenly with anhydrous sodium carbonate at a mixing ratio of 1, and then sintered in a muffle furnace at 950°C for 15h to obtain the positive electrode material Ce-doped BaMnO3 composite ZnO-coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0056] The positive electrode materials obtained in Examples 1 to 7 and Comparative Examples 1 to 4 were assembled into a battery. The positive electrode material: conductive graphite: PVDF mass ratio was 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) was added and continued to grind and stir to form a uniform slurry. The slurry was evenly coated on an aluminum foil with a mold, and the coating thickness was 200 μm. The slurry was placed in a drying oven at 90°C for 10 hours, and then cut into discs with a diameter of 12 mm. The disc was used as the positive electrode, the sodium sheet was used as the negative electrode, the electrolyte included a solvent and NaPF6, wherein the NaPF6 concentration was 1 mol / L, and the solvent of the electrolyte was a mixed solvent of EC, DEC and DMC with a volume ratio of 1:1:1. The battery was assembled in a glove box in the order of button-type battery assembly.

[0057] The assembled batteries were subjected to performance testing. The assembled batteries that had been left to stand overnight were placed in a LAND2001CT battery test box for charge and discharge testing. The test was conducted at 25°C, 1C, and a cycle voltage of 2-4V for 50 cycles.

[0058] Figure 3The data graph of the cycle stability and discharge specific capacity of the positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 after being assembled into batteries shows that, compared with the battery assembled with the positive electrode materials in Comparative Example 1, the cycle stability and discharge specific capacity of the battery assembled with the coated modified positive electrode materials are improved to a certain extent; the positive electrode material prepared in Example 2 has a further improvement in cycle stability and discharge specific capacity compared with the positive electrode material of the BaMnO3 coating layer without Ce doping in Comparative Example 2. The positive electrode material of Ce-doped BaMnO3 composite ZnO as the coating layer in Example 1 has a greater improvement in cycle stability and discharge specific capacity compared with the positive electrode material of Ce-doped BaMnO3 as the coating layer (Example 2) and the positive electrode material of ZnO as the coating layer (Comparative Example 3). In Examples 3 and 4, the doping amount of Ce is mainly changed, and its performance will fluctuate to a certain extent compared with that of Example 1, but it still has good cycle stability and discharge specific capacity.

[0059] Figure 4 The data of the cycle stability and discharge specific capacity of the positive electrode materials prepared in Examples 5 to 7 and Comparative Example 4 after being assembled into batteries are shown in the figure. It can be seen from the figure that when the positive electrode active material is NaNi 2 / 9 Cu 1 / 9 Fe 1 / 3 Mn 1 / 3 O2, using Ce-doped BaMnO3 composite ZnO as the coating layer, its cycle stability and discharge specific capacity are still greatly improved compared with the uncoated positive electrode material. In Example 6 and Example 7, the ratio of Ce-doped BaMnO3 and ZnO powder in the coating layer is adjusted. It can be seen that when the content ratio of Ce-doped BaMnO3 in Example 6 increases, its performance will be slightly reduced compared with Example 5. In Example 7, when the content ratio of ZnO powder increases, its performance will also be reduced to a certain extent; but overall, Example 6 and Example 7 still have good cycle stability and discharge specific capacity.

[0060] Figure 5 The data graph of the cycle stability and discharge specific capacity after the positive electrode materials prepared in Example 8 and Example 9 are assembled into batteries. It can be seen from the figure that when the coating amount and the preparation process parameters change to a certain extent, the performance will fluctuate to a certain extent, but it still has good cycle stability and discharge specific capacity.

[0061] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or additions made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A sodium ion battery cathode material precursor, characterized in that: It comprises a layered hydroxide precursor and a coating layer coated on at least a part of the surface of the layered hydroxide precursor; wherein the coating layer is a Ce-doped BaMnO3 material or a Ce-doped BaMnO3 composite ZnO material.

2. The sodium ion battery cathode material precursor according to claim 1, characterized in that: The molar ratio of Ba, Mn and Ce elements in the Ce-doped BaMnO3 is 1:1-x:x, 0.01≤x≤0.

1.

3. The sodium ion battery positive electrode material precursor according to claim 1, characterized in that: In the Ce-doped BaMnO3 composite ZnO material, the mass ratio of Ce-doped BaMnO3 to ZnO is (1-3):(1-3).

4. The sodium ion battery positive electrode material precursor according to any one of claims 1 to 3, characterized in that: The mass of the coating layer is 1-20% of the mass of the layered hydroxide precursor.

5. The sodium ion battery positive electrode material precursor according to claim 1, characterized in that: The layered hydroxide precursor is one of nickel-iron-manganese hydroxide, nickel-iron-copper-manganese hydroxide, copper-iron-manganese hydroxide, nickel-manganese-copper hydroxide, and nickel-zinc-iron-manganese hydroxide.

6. A method for preparing a sodium ion battery cathode material precursor according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Mix and dissolve a barium source, a manganese source, a cerium source, and a complexing agent in water, stir and mix evenly, heat and evaporate to dryness, and then further dry and calcine to obtain Ce-doped BaMnO3 powder; S2: dispersing Ce-doped BaMnO3 powder or a mixed powder consisting of Ce-doped BaMnO3 powder and ZnO powder in an alcohol solvent to obtain a dispersion; dispersing a layered hydroxide precursor in the dispersion, stirring and evaporating to obtain a solid; after the solid is dried, heating and then keeping warm under a protective atmosphere to obtain a precursor of a positive electrode material for a sodium ion battery.

7. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 6, characterized in that: In the step S1, the barium source, the manganese source, and the cerium source are water-soluble salts of barium, manganese, and cerium, respectively, and the barium source, the manganese source, and the cerium source are added according to a molar ratio of Ba, Mn, and Ce of 1:1-x:x, 0.01≤x≤0.1; The complexing agent is one or more of citric acid, urea and polyethylene glycol, and the ratio of the molar number of the complexing agent to the total molar number of Ba, Mn and Ce ions in the barium source, the manganese source and the cerium source is 1-2:

1.

8. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 6, characterized in that: In step S1, the calcination temperature is 700-1000°C and the calcination time is 10-24h; In step S2, the insulation temperature is 200-400° C. and the insulation time is 0.5-5 h.

9. A sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium ion battery is prepared by mixing the precursor of the positive electrode material of the sodium ion battery according to any one of claims 1 to 5 with a sodium source and then sintering the mixture.

10. A sodium ion battery, characterized in that: It comprises the sodium ion battery positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Positive electrode material of alkali dry battery and preparation method thereof and alkali dry battery

    CN101719547A

  • Ce doped CaMnO3 thermoelectric material and preparation method thereof

    CN105272169A

  • Double-oxide co-coated high-nickel lithium battery positive electrode material and preparation method thereof

    CN108390039A

  • Y-doped CaMnO3 coated ternary positive electrode material and preparation method thereof

    CN108682842A

  • Sodium-ion battery precursor material, positive electrode material and preparation method

    CN115028215A